Novel magnetic resonance imaging approaches to study diseases of gastrointestinal function in children - Sharif, Hayfa (2023)
Background: Gastrointestinal (GI) function in paediatric health and GI disease is a largely unexplored area due to limitations and invasiveness of current techniques. Magnetic resonance imaging (MRI) has been increasingly used to study GI function in adults, but very little has been translated to the paediatric arena to date.